Institutional change in market-liberal state capitalism. An integrative perspective on the development of the private business sector in China - Tobias ten Brink (Max Planck Institute for the Study of Societies, 2011)
This paper shows that a more accurate depiction of the development of China's private sector is gained by considering the complex interaction between bottom-up and topdown processes. First, the paper analyzes the general characteristics of Chinese capitalism to help understand and classify the gradual institutional change in the enterprise sector. Second, it draws on insights from comparative political economy and new approaches in political science to introduce the strategy of 'wearing a red hat,' an empirical phenomenon that provides a framework for the emergence from the 1980s of China's private sector. This section also examines the closely interwoven relationships between private companies and the party-state that have taken place since the 1990s. Third, the paper indicates that focusing on state/capital relationships at different administrational levels contributes to a better understanding of China's private sector. It concludes that the development and success of the new private enterprises, which remained closely linked to the state, enabled the ruling elite to form and consolidate a hegemonic project that provided relative societal coherence on the often bumpy road to reform. – – Dieser Artikel zeigt auf, dass ein Blick auf die komplexen Interaktionen zwischen 'Bottom- up'- und 'Top-down'-Prozessen ein präziseres Bild der Entwicklung des Privatsektors in China liefert. Dabei hilft erstens eine Analyse von grundlegenden Merkmalen des chinesischen Kapitalismus, um den graduellen institutionellen Wandel im Unternehmenssektor verstehen beziehungsweise einordnen zu können. Unter Bezugnahme auf die Vergleichende Politische Ökonomie und neuere politikwissenschaftliche Ansätze werden, zweitens, die empirischen Phänomene des 'wearing a red hat' in der Entstehungsphase des Privatsektors ab den 1980ern sowie der seitdem eng verknüpften Beziehungen zwischen Privatunternehmen und dem Parteistaat eingeführt. Drittens wird erörtert, dass ein Fokus auf die engen Beziehungen zwischen Staat und Kapital auf verschiedenen administrativen Ebenen zu einem besseren Verständnis des chinesischen Privatsektors beiträgt. Wie abschließend festgehalten wird, ermöglichte die Entwicklung und der Erfolg der neuen privaten, jedoch weiterhin eng mit dem Staat verbundenen Unternehmen es der Machtelite, ein hegemoniales Projekt zu formieren und aufrechtzuerhalten, das dem holprigen Reformweg eine relative gesellschaftliche Stabilität verlieh.
Keywords: 300